Molybdenum Sheet Metal Test Device - Ronald Bastovansky; Michal Tropp; Michal Lukac; Frantisek Brumercik (Communications - Scientific letters of the University of Zilina, 2017)
The paper presents the construction of a device that allows processing the Baosteel/Sanchez experiment. The experiment simulates the brake ribs by deep drawing of the molybdenum sheet metal.